Features of research activities in elementary school - Kirgizova A. V. (Modern Problems and Technologies of Innovative Development of Education, 2023)
This study describes the specifics of the implementation of research activities in elementary school. The purpose of this article is to determine the specifics of the organization of research activity of primary school children. The article outlines the component composition of research activity in order to diagnose the corresponding process in elementary school children. The features of research activity, specifically creative nature, scientific, versatility, consistency (or stages) and continuity are highlighted.
Keywords: Исследовательская деятельность; младший школьный возраст; начальная школа; research activities; elementary school age; elementary school